Revisão do gênero Galictis (Mammalia, Carnivora, Mustelidae) utilizando métodos morfológicos e moleculares - Bornholdt, Renata (2012)
Taxonomy forms the basis for all biological sciences, since it is through this discipline that natural units are recognized and described. Without the correct delimitation, researches from other disciplines would be unable to report their results because they would not be sure about the identity of their study units. The current estimate that millions of species are still to be described reinforces the centrality of taxonomy, because is through its use that species are found, delimited and described. Carnivores are usually thought to be well-known mammals, but some of these taxa have not been described yet, while others have received little biogeographic and taxonomic attention, preventing a correct assessment of their richness and conservation status. The genus Galictis (Carnivora, Mustelidae) is an example of a little-studied mustelid from the Neotropics, one of the richest and most endangered regions of the world. Basic information, such as number of species, delimitation between them, diagnosis and geographic distribution, have never been thoroughly tested before, leading to uncertainties regarding the taxonomy of this genus. In order to perform a comprehensive revision of Galictis, morphological and molecular approaches were applied on the basis of records encompassing all the distribution of the genus. For the former approach, we analyzed skulls and skins from 22 zoological collections and the statistical tests showed the presence of two clusters of Galictis specimens, representing G. cuja and G. vittata. Phylogenetic analyses of mitochondrial and nuclear segments supported morphological results showing two monophyletic groups, corresponding again to G. cuja and G. vittata. No other morphological grouping or evidence of a third clade was recognized with our data. All these results corroborate the existence of only two species and indicate morphological characters that effectively diagnose them. These are very useful to identify museum specimens and should also help field-based work in some situations. The correct delimitation between these units allowed the investigation of some long-standing issues about the geographic distribution of Galictis species. For example, we demonstrate the exclusive presence of G. cuja in the northeastern region of Brazil, and established the southernmost limits of G. vittata in the Amazon basin. Finally, as species were well identified and characterized, it was possible to conduct phylogeographic inferences as well as analyses of intra-specific morphological variation in G. cuja. This species contains moderate to high levels of variability and some interesting geographic patterns. These included the morphological distinction of southern Chile and Argentina, the significant genetic structuring among three broad geographic domains, and the evidence of recent demographic expansion in the Brazilian southeast. The results presented here contribute to substantially enhance our knowledge on the genus Galictis, and should help enable further studies focusing on the evolutionary history of these carnivores in the Neotropics.